2004
DOI: 10.1002/hec.892
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of elderly mortality:health status, socioeconomic characteristics and social determinants of health

Abstract: This paper uses longitudinal survey data from Taiwan to investigate the predictors of elderly mortality. The empirical analysis confirms a relationship between socioeconomic characteristics and mortality, but this relationship weakens considerably when estimates are conditional on the health status at the time of the first wave survey. In terms of predictive power, the models with an activities of daily living index fare better (as opposed to models with self-evaluated health or self-reported illnesses). Havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 29 publications
2
28
0
3
Order By: Relevance
“…Deeg and van Zonneveld (1989) assert that there actually is a connection between happiness and longevity using the Dutch Longitudinal Study among the elderly. Mete (2005) finds similar results even for a completely different culture. Analyzing the question of predictors of elderly mortality in a Taiwanese data-set he finds that life-satisfaction in the form of a life-satisfaction index is a good predictor of survival even when health-status and other socio-economic characteristics are taken into account.…”
Section: Life-satisfaction and Happinesssupporting
confidence: 57%
“…Deeg and van Zonneveld (1989) assert that there actually is a connection between happiness and longevity using the Dutch Longitudinal Study among the elderly. Mete (2005) finds similar results even for a completely different culture. Analyzing the question of predictors of elderly mortality in a Taiwanese data-set he finds that life-satisfaction in the form of a life-satisfaction index is a good predictor of survival even when health-status and other socio-economic characteristics are taken into account.…”
Section: Life-satisfaction and Happinesssupporting
confidence: 57%
“…Even when controlling for confounders and other known predictors, such as age and gender, the instrument could significantly predict mortality. Mete (2005) also found that measures like the ADL index are good predictors of mortality among the elderly (60+) in general. Furthermore, Sonn (1996) found that the ADL-staircase could be used to predict mortality among older people.…”
Section: This Indicates That the External Validity Of The Present Stumentioning
confidence: 93%
“…Thus, the range of values for wealth was 0e3, where higher values indicated greater wealth. Similar household wealth measures have been used in previous literature (for example, Mete, 2005;Galobardes et al, 2007). Self-perceived economic satisfaction was a dichotomous variable determined according to the question, "How do you rate your household economic status?"…”
Section: Measurementsmentioning
confidence: 99%